2003
DOI: 10.1053/ejvs.2002.1873
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered bioprosthetic venous valve: A long-term study in sheep

Abstract: acellularisation and consecutive in vitro autogeneic re-seeding of valved venous conduits can lead to immunologically acceptable, patent, and competent implants in sheep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 15 publications
1
55
0
Order By: Relevance
“…9 In particular in the field of heart valve regeneration, several recent preclinical large animal trials involving sheep 14,15,17 and non-human primate models 16 showed promising initial results and underline the potential of this technology for future therapeutic concepts. Given the major complications when using xeno-or homogenic venous valve transplants, Teebken et al 37 investigated for the first time TEVVs based on a homologous decellularized matrix in the ovine model. After removal of cellular elements, the valves were repopulated with autologous myofibroblasts and implanted into the external jugular veins with patency up to 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…9 In particular in the field of heart valve regeneration, several recent preclinical large animal trials involving sheep 14,15,17 and non-human primate models 16 showed promising initial results and underline the potential of this technology for future therapeutic concepts. Given the major complications when using xeno-or homogenic venous valve transplants, Teebken et al 37 investigated for the first time TEVVs based on a homologous decellularized matrix in the ovine model. After removal of cellular elements, the valves were repopulated with autologous myofibroblasts and implanted into the external jugular veins with patency up to 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Previously described general animal care guidelines were followed (12). One or two sheep were studied per day.…”
Section: Discussionmentioning
confidence: 99%
“…Conduit patency requires the following: the conduit must have antithrombotic properties [13]; intima hypertrophy must not progress in anastomoses between the MPA and the conduit [29], the intima should be covered with neo-endothelial cells [30] and the flexibility and histological form of the valve in the conduit should be maintained [27]. Although Denacol exerts an antithrombotic effect [19], intima hypertrophy in anastomoses has been demonstrated in humans due to delayed healing of the vessel after positioning a small-caliber artificial vascular graft treated with antithrombotics [22].…”
Section: Discussionmentioning
confidence: 99%